Analysis of Inventory Calculation Between the Just In Time Method and the Economic Order Quantity Method at PT. Ohtomi Indonesia: Just In Time Method and the Economic Order Quantity Method at PT. Ohtomi Indonesia - Winda Natalia Pardede; Lembah Dewi Andini; Diana Airawaty; Sistya Rachmawati (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2025)
At company PT. Ohtomi, there is a discrepancy between theory and practice in the application of inventory control methods. Theoretically, the Just In Time (JIT) method should be able to reduce storage costs since the company does not need to maintain large stock. However, field data shows that inventory costs under the JIT method are actually higher compared to the Economic Order Quantity (EOQ) method.